Do patient experiences have mediating roles on patient loyalty - ÇANDERELİ, ZEHRA ÖZGE; MUMCU, GONCA (My University, 2022)
The study aimed to evaluate the mediating roles of patient experiences on patient loyalty. The data were collected through an electronic questionnaire regarding feedback from 5732 patients received outpatient clinics. Patient loyalty was evaluated using the Net Promoter Score (NPS11) that patients were asked whether they would like to recommend the hospital to their relatives or friends. Patient experiences with physicians, nurses, and waiting times were also asked in the questionnaire. After preliminary analysis, mediation analyses were performed to evaluate direct and indirect causal effects among variables for NPS11. While patient experiences are used as possible mediators, Branch Groups in the first and Admission Time in the second model are independent variables. In the analyses, Surgical Medical Science (p = 0.019) and Day Shift (p = 0.000) have a direct mediating effect on NPS11. Nursing care experiences were found to be a mediator variable for NPS11 in both models (p = 0.000 for both). Patient loyalty was associated with Surgical Medical Science and Day Shift primarily whereas Nursing care experience had a mediating role.
Keywords: SAĞLIK BAKIM BİLİMLERİ VE HİZMETLERİ; Klinik Tıp; Klinik Tıp (MED); HEALTH CARE SCIENCES & SERVICES; CLINICAL MEDICINE; Clinical Medicine (MED); patient loyalty; patient experience; Net Promoter Score; mediation analysis; private hospital; NET PROMOTER SCORE; SATISFACTION; NURSE; OUTCOMES; patient loyalty; patient experience; Net Promoter Score; mediation analysis; private hospital